Pengaruh Pemanfaatan Media Colour Corrugated Paper (kokoru) Terhadap Kemampuan Anak Usia 4-5 Tahun Di TK Pembinaan Pasir Putih - Oktavia, Suci Deta; Yunesti, Dilla (ICEJ : Islamic Childhood Education Journal, 2023)
This thesis focuses on the effect of using colored corrugated paper (kokoru) media on the fine motor skills of children aged 4-5 years at the Pangkalpinang Pasir Putih Development Kindergarten, where some children have relatively low fine motor skills. This research is a quantitative descriptive study that seeks the influence of kokoru media on the fine motor skills of children aged 4-5 years at the Pangkalpinang Pasir Putih Development Kindergarten. By collecting data through documentation and questionnaires, the data collection technique was then tested using the data normality test and the non-parametric U Mann Whitney test. The results of this research show that there is an influence of kokoru media on the fine motor skills of children aged 4-5 years at the Pangkalpinang Pasir Putih Development Kindergarten. Where Kokoru media has an effect on improving fine motor skills, this can be seen from the results of non-parametric tests using the Mann Whitney U test which obtained Sig results. 0.000 < 0.05 which means the hypothesis is accepted. So, it can be said that kokoru media has an influence on improving the fine motor skills of children aged 4-5 years at the Pangkalpinang Pasir Putih Development Kindergarten.